Execução de compras de produtos para alimentação escolar pelas prefeituras da região metropolitana de São Paulo e agricultores familiares contemplados - Rocha, Bruna da [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In 2009, Federal Law 11,947 was approved, regulating the National School Feeding Program and giving greater institutionality to this public policy. One of the aspects of the new legislation was the orientation for its executing agents to reinforce the nutritional value of school meals, prioritizing the use of fresh products or products with a minimum degree of processing. It made it mandatory, through Article 14 (A14), that at least 30% of federal transfers for school meals intended for federative entities be spent on products from family farming, giving priority to farmers in the municipality or region. The objective is to verify how the 39 city halls of the Metropolitan Region of São Paulo carried out, in 2018 and 2019, the A14, in terms of the level of compliance and adequacy of the purchasing processes to the conditions of family farmers. The established commercial flows were also mapped, considering farmers from the RMSP itself, from other regions of the state, or from other states. Municipal public calls for the purchase of products from family farmers and the provision of accounts for school meals in the 39 municipalities with the National Education Development Fund were analyzed. It is concluded that public notices were adequate for family farmers, but compliance with A14 had deficiencies and inadequacies. Several municipalities did not spend the mandatory 30% and a significant percentage of purchases were carried out with farmers from other states, the especially Rio Grande do Sul. In this sense, the idea of circulating federal resources in the RMSP itself and promoting local development remained far from being achieved.

Em 2009, foi aprovada a Lei Federal 11.947, regulamentando o Programa Nacional de Alimentação Escolar (PNAE) e dando maior institucionalidade a essa política pública. Um dos aspectos da nova legislação foi a orientação para seus agentes executores reforçarem o valor nutricional da alimentação escolar, priorizando o uso de produtos in natura ou com mínimo grau de processamento. Tornou obrigatório, através do Artigo 14 (A14), que no mínimo 30% dos repasses federais para a alimentação escolar destinados aos entes federativos fossem gastos com produtos oriundos da agricultura familiar, dando-se prioridade aos agricultores do próprio município ou região. Tem-se como objetivo verificar como as 39 prefeituras da Região Metropolitana de São Paulo (RMSP) executaram, em 2018 e 2019, o A14, em termos de nível de cumprimento e adequação dos processos de compra às condições dos agricultores familiares. Também se mapearam os fluxos comerciais estabelecidos, considerando-se agricultores da própria RMSP, de outras regiões do estado ou de outros estados. Foram analisadas chamadas públicas municipais para compra de produtos de agricultores familiares e as prestações de conta da alimentação escolar dos 39 municípios junto ao Fundo Nacional de Desenvolvimento da Educação. Conclui-se que as chamadas públicas se mostraram adequadas aos agricultores familiares, mas o cumprimento do A14 apresentou deficiências e inadequações. Vários municípios não gastaram os 30% obrigatórios e porcentagem significativa das compras foi executada junto a agricultores de outros estados, em especial do Rio Grande do Sul. Neste sentido, a ideia de fazer circular os recursos federais na própria RMSP e promover o desenvolvimento local ficou distante de ser alcançada.
Execution of purchases of products for school meals by the municipalities of the metropolitan region of São Paulo and contemplated family farmers
Keywords: Public policies; Agricultura familiar; Políticas públicas; Merenda escolar